2021
DOI: 10.1111/jfpp.15719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluidized‐bed and freeze‐drying techniques on physicochemical, nutritional, thermal, and structural properties of Moringa oleifera flowers, leaves, and seeds

Abstract: Moringa oleifera Lam. (Moringaceae) is called a "Miracle Tree" with multiple medicinal and industrial applications. This tree has originated in India and is cultivated in tropical and sub-tropical countries. Almost all the parts of this plant are valuable and edible as they high nutritional and medicinal values (Arora et al., 2013). It is the most abundant source of minerals, vitamins, amino acids, and phytochemicals such as phenols, ascorbic acid, and flavonoids that are important for its high antioxidant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
0
5
0
Order By: Relevance
“… GMDgoodbreak=LWT13 normalΦgoodbreak=()()LWT1/3/normalL ARgoodbreak=normalL/normalW The projected area of a single fruit is a good indicator of mass. The projected area can be used for designing the grader and also used for accurate modeling of heat and mass transfer analysis during drying and cooling (Manju, Rekha, & Kumar, 2021). The projected areas of strawberries in three perpendicular dimensions viz., PA L , projected area perpendicular to the length (mm 2 ); PA W , projected area perpendicular to the width (mm 2 ); PA T , projected area perpendicular to the thickness (mm 2 ), were measured by using a camera and Fiji ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“… GMDgoodbreak=LWT13 normalΦgoodbreak=()()LWT1/3/normalL ARgoodbreak=normalL/normalW The projected area of a single fruit is a good indicator of mass. The projected area can be used for designing the grader and also used for accurate modeling of heat and mass transfer analysis during drying and cooling (Manju, Rekha, & Kumar, 2021). The projected areas of strawberries in three perpendicular dimensions viz., PA L , projected area perpendicular to the length (mm 2 ); PA W , projected area perpendicular to the width (mm 2 ); PA T , projected area perpendicular to the thickness (mm 2 ), were measured by using a camera and Fiji ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, aspect ratio and moisture content imperatively affected the frictional and mechanical properties of moringa. So far, research studies have reported only on changes in quality, nutritional and textural attributes of moringa leaf powder using different drying techniques and various drying temperatures (Premi et al, 2012; Saini et al, 2014; Verma et al, 2015; Looi et al, 2019; Manju et al, 2021), frictional properties of moringa pods (Sudagar et al, 2021), and moisture‐dependent physical properties of moringa seeds (Aviara et al, 2013). There were no investigations on the frictional and mechanical characteristics of moringa pods concerning to aspect ratio and moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…(2022), the antioxidant activity of the methanolic extract of Moringa oleifera flower was observed to be 56.95 ± 0.77 μg/mL. The antioxidant activity of the flower extract might be due to the presence of phenolic and flavonoid compounds in the extract (Manju et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen was used as carrier gas at a rate of 20 mL/min. The sample was held at 600 °C for a minute, then the weight changes were observed in the form of a graph, and the values were collected (Balogun et al ., 2021; Manju et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%